Pessimism of Dimitrijе Kantakuzin and Serbian Modernists Dis and Pandurović (Comparative analysis) - Milentijević, Tijana (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Although pessimism, which is the dominant motif of modernist poetry, is considered to have originated under the influence of Western models, we must not forget that it appeared in the Serbian literature of the Middle Ages. The motives of the transience of life, sin, anticipation of death, despair, and fear can be traced from the very beginnings of the formation of the original Serbian literature and were an expression of various social and historical troubles that gripped the Serbian people. This paper aims to examine how pessimism was realized in the poem Molitva Bogorodici by Dimitrij Kantakuzin and the poets of the Serbian modernism. The need to write this paper arose from the desire to determine the origin of the influence of the motif of the transience of life and death in the poetry of the Middle Ages on the one hand, and modernist poets, on the other.